First record of the vulnerable social parasite ant Plagiolepis grassei in Italy (Hymenoptera: Formicidae) - Schifani, Enrico (Fragmenta entomologica, 2017)
The first Italian records of the rare parasitic ant species Plagiolepis grassei Le Masne, 1956 are here reported. This species is considered as “Vulnerable” by the IUCN’s Red List, and was previously recorded from France and Spain only.